THE FORMATION AND DEVELOPMENT STAGES OF LINGUOCULTURAL STUDIES IN MODERN LINGUISTICS (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the formation and development of linguocultural studies within the framework of modern linguistics. The research traces the evolution of the discipline from its philosophical foundations in the 19th century to its establishment as an independent interdisciplinary field in the late 20th century. Special attention is paid to the anthropocentric paradigm, which reoriented linguistic research toward the human factor, cognition, and culture. The article also outlines key theoretical contributions, major scholars, and contemporary applications of linguoculturology in intercultural communication, translation studies, and global discourse analysis.
Keywords: linguoculturology, anthropocentric paradigm, linguistic worldview, cultural concept, Sapir–Whorf hypothesis, intercultural communication.